ANALYSIS OF EXCHANGE RATE FLUCTUATION USING VECTOR ERROR CORRECTION MODEL (VECM) FROM 2010 TO 2015 - Fitra Prasapawidya Purna (EKPI 16 UMY 249, 2016)
Exchange rate in the last few years has been fluctuating highly. A number of variables were used in this research to analyze which variable has impact on exchange rate. The variables used were export, import, money supply and Bank Indonesia rate, for the period of January 2010 until September 2015, utilizing Vector error correction model or VECM estimation method. The results indicate that in the long-run, some variables such as import and money supply have significant correlations to ER with positive and negative impact respectively, while export and BI rate have no significant correlation to ER with negative and positive impact respectively. In the short-run, all variables bear significant influence on ER except money supply, whereas import, money supply and BI rate maintain a positive relationship with the ER. Meanwhile, export has a negative influence on ER. For impulse response and forecast error variance decomposition, the variable which induced the most shock to exchange rate was import. Keywords: Exchange rate, Export, Import, Money supply, Bank Indonesia rate, VECM